THE EFFECT OF INTERNET BANKING SERVICE QUALITY ON CUSTOMER SATISFACTION LEVEL OF PT BANK MANDIRI (PERSERO) TBK KCP MEDAN KIRANA - Bertha Nerpy Siahaan (SEAN Institute, 2022)
The research entitled “The Effect of Internet Banking Service Quality on Customer Satisfaction of PT. Bank Mandiri (Persero) Tbk KCP Medan Kirana